2008
DOI: 10.1128/aac.00653-08
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Evaluations of Oxacillin Efficiency against mecA -Positive Oxacillin-Susceptible Staphylococcus aureus

Abstract: Community-type Staphylococcus aureus strains that are positive for mecA and PBP2a but appear phenotypically susceptible to oxacillin are increasingly reported worldwide. Four S. aureus clinical isolates carrying the mecA gene with oxacillin MICs of <2 g/ml were tested for oxacillin efficiency by population analyses and experimental thigh infections. These isolates harbored staphylococcal cassette chromosome mec type IV and belonged to two genotypes. Two of the four isolates were found by population analysis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 17 publications
(27 reference statements)
3
25
0
1
Order By: Relevance
“…been reported (55,82,83,86). Although mecA expression is normally a prerequisite for methicillin resistance, mecA expression alone does not appear to be sufficient to guarantee phenotypic methicillin resistance, which suggests the existence of additional molecular targets that could be associated with the susceptibility to oxacillin in certain strains (83).…”
Section: Pbp 2a: the Sole Determinant Of Methicillin Resistance?mentioning
confidence: 99%
“…been reported (55,82,83,86). Although mecA expression is normally a prerequisite for methicillin resistance, mecA expression alone does not appear to be sufficient to guarantee phenotypic methicillin resistance, which suggests the existence of additional molecular targets that could be associated with the susceptibility to oxacillin in certain strains (83).…”
Section: Pbp 2a: the Sole Determinant Of Methicillin Resistance?mentioning
confidence: 99%
“…Though it can detect true MRSA effectively, it is likely to miss mecA-positive S. aureus having an oxacillin MIC of Ͻ2 g/ml. Such isolates have been considered to be extremely heteroresistant (Ͻ1 in 10 8 of the population is highly resistant to methicillin), but there are also reports documenting the existence of nonheterogeneous phenotypically oxacillin-susceptible mecA-positive S. aureus (OS-MRSA) (6). The use of ␤-lactams to treat such isolates may cause an increase in the MIC of oxacillin well above the established breakpoint for resistance (oxacillin MIC, Ն4 g/ml), ultimately leading to failure of therapy (10).…”
mentioning
confidence: 99%
“…Among the MRSA isolates, only a few express homogeneous oxacillin resistance (i.e., Ն1 in 10 2 express high-level resistance) while the majority show heterogeneous drug resistance (heteroresistance) (3). Phenotypically oxacillin-susceptible and mecA-positive S. aureus clinical isolates are being increasingly reported (4)(5)(6)(7)(8)(9)16). Dependence on growth conditions like temperature and osmolarity of the medium for phenotypic expression of resistance further complicates susceptibility testing of MRSA by standard microbiological methods (3).…”
mentioning
confidence: 99%
“…Hososaka et al described six OS-MRSA isolates in Japan, with two-thirds of the isolates having SCCmec type III and none of the isolates containing PVL or enterotoxin (7). In vitro and in vivo studies have confirmed that OS-MRSA isolates that contain mecA and express PBP2a are functionally oxacillin resistant in time-kill curves and in a mouse model with experimental thigh infections (8,15). This raises the important question of how often are these strains missed in the clinical laboratory?…”
mentioning
confidence: 89%